2023
DOI: 10.1111/ene.15869
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Tarlov cysts: Neurophysiology abnormalities and correlation with pelvic sensory and visceral symptoms

Abstract: Background and purpose Recent studies suggest a possible association between Tarlov cysts (TCs), usually considered as incidental radiological findings, and neurological symptoms such as pain, numbness and urogenital complaints. The aim was to explore the relationship between TCs and sacral nerve root functions using pelvic neurophysiology tests, and to correlate changes with clinical symptoms and magnetic resonance imaging (MRI) findings. Methods Consecutive patients with sacral TCs, referred for pelvic neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Symptoms disappeared after surgical removal of the cysts. Hentzen C et al [11] included 65 women and after analysis found that various symptoms caused by sacral cysts were associated with sacral somatic nerve injury.…”
Section: Clinical Symptoms and Diagnosismentioning
confidence: 99%
“…Symptoms disappeared after surgical removal of the cysts. Hentzen C et al [11] included 65 women and after analysis found that various symptoms caused by sacral cysts were associated with sacral somatic nerve injury.…”
Section: Clinical Symptoms and Diagnosismentioning
confidence: 99%